Going concern SMEs in Covid-19 pandemic era: a lesson learned from Indonesia - Marsdenia (JBFEM, 2023)
This article objectives to explore a new insight related to a way of SMEs in Indonesia to survive during pandemic Covid-19, location at Depok city, in West Java Province. As we knowed, there are so many business entity impacted in this situation of Covid-19 pandemic, where the business entity should agreed to tight health protocol related to maintain the health of community. The consequencies of pandemic condition to communityÂ should have a new daily activity behavior in the new normal era and could handle the business from home and stay at home, reduced mobility and wear mask during out door activity. Fortunately, era 4.0 and society 5.0Â famous with digitalization transformation inÂ the various aspects in the society behavior. The digitalization transformations provide an opportunity to business entity going concern by doing virtual business and promoting their products through online tools to borderless country. This article try to answer the questions through qualitative method and descriptive analysis approach to explore and confirmed those answering. Indepth interview to some key informants such as SMEs actor, customer or SMEs products and also the regulator body. The study revealed the collaboration among SMEs actor to produce and market their product through digitalization be a the best way and a key of success to survive in the era covid-19 pandemic. Collaboration tends to achieved economic efficiency in running business.